Madurese Language Syllabus Development as Local Content Using a Content and Language Integrated Learning (CLIL) Approach in Elementary Schools - et. al., Imamah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Local language instruction as a local material needs successful renewal, such that educational organizations can maintain the district language as a cultural legacy. The purpose of the study was to create a Madurese language syllabus as local material using the CLIL method to improve the learning process in elementary schools. The study employed the research and creation approach, which applies to Lee and Owens' four phases (needs analysis, designing, developing, implementing, and evaluating). The Madurese language syllabus the product met the criteria based on the findings of two experts and four practitioners through test objects, information, and face validity (all validators in each aspect agreed that the product was ready to be implemented in learning). Furthermore, the results of analytical validation through student feedback in small group trials were positive (the acquisition of the percentage of each component receives excellent interpretation). The established syllabus could effectively facilitate the learning of local material of elementary schools in the Pamekasan district